Echoes from Freire for a critically engaged pedagogy - Mayo, Peter, 1955- (Critical pedagogy today series., 2013)
In this concise and accessible text, Peter Mayo outlines some of the major concepts in Freire's praxis. In pursuit of a critically engaging pedagogy, Mayo compares Freire's work with a range of other thinkers and educators, including Lorenzo Milani, Antonia Darder, John Dewey, Margaret Ledwith, Antonio Gramsci, and Henry Giroux. Chapters in the book include discussions of the State's role in education - specifically higher education; a critical analysis of the dominant discourse in education centering on 'competences' and the type of slant this discourse takes; a study of adult education throu.